Vascularization and nutrient delivery at root-knot nematode feeding sites in host roots - Bartlem, Derek G; Jones, Michael G. K; Hammes, Ulrich Z (Journal of experimental botany, 2014)
Plants are constantly challenged by pathogens and pests, which can have a profound impact on the yield and quality of produce in agricultural systems. The vascular system of higher plants is critical for growth and for their ability to counteract changing external conditions, serving as a distribution network for water, nutrients, and photosynthates from the source organs to regions where they are in demand. Unfortunately, these features also make it an attractive target for pathogens and pests that demand access to a reliable supply of host resources. The vascular tissue of plants therefore often plays a central role in pathogen and parasite interactions. One of the more striking rearrangements of the host vascular system occurs during root-knot nematode infestation of plant roots. These sedentary endoparasites induce permanent feeding sites that are comprised of ‘giant cells’ and are subject to extensive changes in vascularization, resulting in the giant cells being encaged within a network of de novo formed xylem and phloem cells. Despite being considered critical to the function of the feeding site, the mechanisms underlying this vascularization have received surprisingly little attention when compared with the amount of research on giant cell development and function. An overview of the current knowledge on vascularization of root-knot nematode feeding sites is provided here and recent advances in our understanding of the transport mechanisms involved in nutrient delivery to these parasite-induced sinks are described.